Peran Guru PAI Dalam Membentuk Karakter Religius Siswa Di SD IT DOD Medan - Rahmat Hidayat Nasution; Nurhalimah Tambunan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to determine the role of teachers in shaping students' religious character, the methods used and the process of forming students' religious character at SD IT DOD Medan. The method in this study is descriptive qualitative with a case study approach. Data collection techniques in this study were carried out by means of observation, interviews and documentation to four research informants, namely the principal, 2 Islamic Religious Education teachers and 1 fourth grade student ABY. The results of this study indicate that 1). The role of teachers in shaping students' religious character is the role of teachers as educators and instructors, the role of teachers as guides, the role of teachers as motivators, the role of teachers as evaluators and the role of teachers as role models. 2). The methods used in shaping students' religious character are the habituation method and the exemplary method. 3). The process of forming students' religious character is carried out through several stages, namely the habituation stage, the understanding stage, the application stage and the coercion stage.